Litter production in Holm oak trees subjected to different pruning intensities in Mediterranean dehesas - Andivia, Enrique; VÁZQUEZ-PIQUÉ, JAVIER; FERNÁNDEZ, MANUEL; Alejano, Reyes (Agroforestry systems, 2012)
Litterfall is a key process in forests which is sensitive to climatic conditions like precipitation and temperature, and management practices. Therefore, knowledge about litterfall patterns and its associated variables is important for the conservation of Mediterranean ecosystems under conditions of climate change. We aimed to quantify the temporal pattern of litterfall and to investigate the inﬂuence of abiotic variables and pruning on litter production. Litterfall was collected at monthly intervals for 2 years in trees subjected to different pruning intensities in two locations. The effect of pruning, abiotic variables and tree size on litter production was analyzed using a mathematical model. Leaf fall was strongly seasonal with a peak occurring in the wettest month of the year in this area. The variability in leaf fall was mainly related to rainfall and soil water in 2 years and locations. Pruning reduced the amount of litter production during the ﬁrst year following this practice, and might have negative effect on soil fertility and crop productivity in dehesas ecosystems.
Keywords: á agroforestry systems; á litterfall á; agroforestry systems; climate change; climate change á management; litterfall; management; pruning; Quercus ilex; quercus ilex á pruning